Boarding-out of pauper children - Tod, Isabella M. S. (Statistical and Social Inquiry Society of Ireland, 1879)
The mode of dealing with those children who are cast entirely upon the care of the state, which is known as boarding-out, is not a new one, either in principle or practice, although it has attracted more attention during the last few years, and been considerably extended. Indeed it would have been surprising had it been left to us now to discover such a plan; for it is surely the one which would most naturally suggest itself to any thinking mind and feeling heart. If a child is placed in a position so unchildlike as to have neither parents nor any relative to take the parent's place, is it not the first thought of any onlooker to put it into the hands of those who will try to be father and mother to it. It could never occur spontaneously to any one, that if you got for this poor little shivering body and frightened soul the one hundredth part of a matron's care, and the one hundredth part of a schoolmaster's, and the one thousandth part of a relieving officer's, that you had done all that was necessary to bring up this creature to the stature of a healthy, intelligent, useful man or women. Human beings do treat each other humanly, until they are withdrawn from sight, and arranged for in such huge masses as to smother individual feeling.
Read before the Society, August 1878
Keywords: Children; Orphanages; Child welfare; 314.15